Concomitant disorder and high‐affinity zinc binding in the human zinc‐ and iron‐regulated transport protein 4 intracellular loop. (12th March 2019) - Bafaro, Elizabeth M.; Maciejewski, Mark W.; Hoch, Jeffrey C.; Dempski, Robert E.
Abstract: The human zinc‐ and iron‐regulated transport protein 4 (hZIP4) protein is the major plasma membrane protein responsible for the uptake of zinc in the body, and as such it plays a key role in cellular zinc homeostasis. hZIP4 plasma membrane levels are regulated through post‐translational modification of its large, disordered, histidine‐rich cytosolic loop (ICL2) in response to intracellular zinc concentrations. Here, structural characteristics of the isolated disordered loop region, both in the absence and presence of zinc, were investigated using nuclear magnetic resonance (NMR) spectroscopy. NMR chemical shifts, coupling constants and temperature coefficients of the apoprotein, are consistent with a random coil with minor propensities for transient polyproline Type II helices and β‐strand in regions implicated in post‐translational modifications. The ICL2 protein remains disordered upon zinc binding, which induces exchange broadening. Paramagnetic relaxation enhancement experiments reveal that the histidine‐rich region in the apoprotein makes transient tertiary contacts with predicted post‐translational modification sites. The residue‐specific data presented here strengthen the relationship between hZIP4 post‐translational modifications, which impact its role in cellular zinc homeostasis, and zinc sensing by the intracellular loop. Furthermore, the zinc sensing mechanism employed by the ICL2 protein demonstrates that high‐affinity interactions can occur in the presence of conformational disorder.